2017
DOI: 10.21577/0103-5053.20170077
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of LiCoO2 from Different Precursors by Sol‑Gel Method

Abstract: Lithium cobalt oxide, LiCoO 2 , widely used as cathode in lithium ion batteries was synthesized and their structural and electronic properties investigated. The crystalline powders were prepared by the sol-gel method with four complexing agents: citric acid, glycine, starch and gelatin. These syntheses were compared with the blank test (without complexing agent). The X-ray diffraction and vibrational spectroscopy allowed the identification of the rhombohedral phase LiCoO 2 ( ) as the only or principal crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
2
4
0
Order By: Relevance
“…6B-6E). This agrees with Okubo et al results [44,45], in which the electron diffraction patterns revealed the characteristic geometry of an oxide structure along atomic layers.…”
Section: Intensity (Au)supporting
confidence: 92%
“…6B-6E). This agrees with Okubo et al results [44,45], in which the electron diffraction patterns revealed the characteristic geometry of an oxide structure along atomic layers.…”
Section: Intensity (Au)supporting
confidence: 92%
“…56 In addition, the characteristic band of the spinel Co 3 O 4 at around the 690 cm −1 is not observed in Raman spectra, which suggests there is no Co 3 O 4 impurity in the as-prepared cathode materials. 58 The Raman spectral results suggest that LiCoO 2 with α-NaFeO 2 layered structure and without any impurity are synthesized, and the crystalline structure and purity of LiCoO 2 is not affected by addition of Ag, agreeing well with XRD results.…”
Section: Resultssupporting
confidence: 76%
“…4d are attributed to the Co-O stretching Eg modes and the O-Co-O vibrational A1g modes of LiCoO 2 with ordered α-NaFeO 2 layered structure, respectively. 56,58 While four Raman bands for LiCoO 2 with spinel structure are not observed in the as-prepared products. 56 In addition, the characteristic band of the spinel Co 3 O 4 at around the 690 cm −1 is not observed in Raman spectra, which suggests there is no Co 3 O 4 impurity in the as-prepared cathode materials.…”
Section: Resultsmentioning
confidence: 92%
“…These powders exhibit a rhombohedral crystalline structure (ICSD 98-004-8103) characteristic of LiCoO 2 [17] [18] [19] with no secondary phases. The space group associated with this structure is R-3m (166), known as a high-temperature structure, or HT-LiCoO 2 [20]; it is formed of alternating cobalt and lithium layers with oxygen anions, as reported by Bruno et al [21]; a schema of this structure is shown in Figure 1(b).…”
Section: Structural Propertiesmentioning
confidence: 63%